2021
DOI: 10.1038/s41598-021-99531-2
|View full text |Cite
|
Sign up to set email alerts
|

Compartment specific regulation of sleep by mushroom body requires GABA and dopaminergic signaling

Abstract: Sleep is a fundamental behavioral state important for survival and is universal in animals with sufficiently complex nervous systems. As a highly conserved neurobehavioral state, sleep has been described in species ranging from jellyfish to humans. Biogenic amines like dopamine, serotonin and norepinephrine have been shown to be critical for sleep regulation across species but the precise circuit mechanisms underlying how amines control persistence of sleep, arousal and wakefulness remain unclear. The fruit fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 102 publications
0
17
0
Order By: Relevance
“…While Nf1 is broadly expressed throughout the brain, its function has been linked to the modulation of GABA signaling during the formation of associative memories (Georganta et al, 2021). In Drosophila, the GABAA receptor Resistant to dieldrin (Rdl) is expressed in numerous populations of sleep-regulating neurons (Fig 4A; Chung et al, 2009;Driscoll et al, 2021;Parisky et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While Nf1 is broadly expressed throughout the brain, its function has been linked to the modulation of GABA signaling during the formation of associative memories (Georganta et al, 2021). In Drosophila, the GABAA receptor Resistant to dieldrin (Rdl) is expressed in numerous populations of sleep-regulating neurons (Fig 4A; Chung et al, 2009;Driscoll et al, 2021;Parisky et al, 2008).…”
Section: Resultsmentioning
confidence: 99%
“…While Nf1 is broadly expressed throughout the brain, its function has been linked to the modulation of GABA signaling during the formation of associative memories (Georganta et al, 2021). In Drosophila , the GABA A receptor Resistant to dieldrin (Rdl) is expressed in numerous populations of sleep-regulating neurons (Fig 4A; Chung et al, 2009; Driscoll et al, 2021; Parisky et al, 2008). To examine whether Nf1 functions in GABA A receptor neurons, we selectively knocked down Nf1 by expressing Nf1 RNAi under the control of Rdl -GAL4 and then measured its effect on sleep.…”
Section: Resultsmentioning
confidence: 99%
“…For over two decades, Drosophila has been utilized as a model system to study sleep (14,15) and both serotonin (16)(17)(18)(19)(20) and dopamine (21)(22)(23)(24)(25) have been shown to play significant roles in regulating sleep duration and quality. A role for serotonin in promoting sleep in Drosophila has been demonstrated in part by feeding the precursor 5-hydroxytryptophan (5-HTP) (16) or by utilizing mutants for the serotonin rate-limiting synthetic enzyme tryptophan hydroxylase (TRH) (20).…”
Section: Introductionmentioning
confidence: 99%
“…The PAM cluster comprises ~130 neurons per hemisphere, accounting for approximately 80% of fly brain DA neurons. PAM neurons are highly heterogeneous in their projection patterns and functions and play critical roles in behavioral processes such as olfactory associative learning, foraging, sleep, and locomotion [14][15][16][17][18] . We and others showed that loss of a subclass of PAM neurons leads to defective startle-induced climbing behavior in several PD models 13,19,20 , suggesting a partial analogy between the PAM cluster and the substantia nigra pars compacta.…”
Section: Introductionmentioning
confidence: 99%